Reframing Siswa Hafiz Quran dengan Self-Efficacy Rendah: Praktik Baik di Madrasah Aliyah Negeri - Istiqomah, Febrianti Nur; Utami, Indah Ismi; Munawaroh, Siti Rofiatul; Ardiansyah, Mochammad Zaka (Jurnal Penelitian Pendidikan Islam, 2022)
This study aims to determine the low self-efficacy of hafiz Al-Qur’an students. Implementation of good guidance practices for hafiz Al-Qur’an students with reframing techniques at MAN 1 Jember. The main informants of this descriptive qualitative research are teachers and students. Informants were selected using a purposive sampling technique by deliberately selecting religious subject teachers who practice good guidance to hafiz Al-Qur’an students. In this working paper, all student informants’ names are pseudonymous. In addition to semi-structured interviews, the author also extracted data from students’ digital report cards, guidance and counseling teacher notes, and students’ Al-Qur’an memorization notes. This study reports that the client’s form of low self-efficacy is procrastination in memorizing the Qur’an caused by low self-control, lack of self-confidence and affection from both parents, experiencing post-traumatic after their parents divorced, and being lazy to do muraja’ah (repetition of re-reading) of the Qur’an so that there is a feeling of “fear of being wrong” and fear of forgetting when reporting the memorization of the Qur’an to the teacher, as well as during the learning of Al-Qur’an Hadith. Students also often seem confused when explaining back the material they are learning. This study also found that Al-Qur’an Hadith teachers play an active role in providing guidance from the beginning of the first semester twice a month, by framing the client’s thoughts that lead to low self-efficacy. Although not yet getting the maximum change, but after three months of carrying out guidance, changes in client behavior have appeared after they are willing to read their memorized Al-Qur’an in front of the teacher.